PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - MARDI ASTUTIK (STIE Indonesia Malang, 2016)
AbstractAssessment of performance is the organizational process in assessing theperformance of employees is done with the purpose to provide feedback toemployees in an effort to improve the appearance of its work and efforts to increasethe productivity of the organization, and in particular carried out in relation tovarious policies to employees as to the purpose of promotion, a raise, education andtraining and others. The goal of this research is to analyze:1) the effect ofcompensation on employee performance, 2) The effect of labor discipline effect onemployee performance, partially or simultan The type of research wasexplanatory. The population in the research was the employee of PT SejahteraUsaha Bersama (PT SUB) in production department, by involving 71 respondentas samples. The kind of analysis using multiple linear regression. Based on theresults, it can be concluded that the compensation and discipline has positiveinfluence on employee performance, partially and simultan.Keywords: Employee performance, compensation, work discipline